TED Talks as a Learning Medium to Improve Listening Skills of Vocational School Students - Agustino, Novrada Julian; Gozali, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
Utilizing TED Talks videos provides a fresh and attractive experience for students, enhanced by their accessibility across various platforms, which simplifies the learning process for them. A variety of videos, such as those from TED Talks, can serve as useful resources for acquiring the English language. This investigation focuses on enhancing students' listening abilities through the utilization of TED Talks videos. This investigation employed a pre-experimental design to examine the issue. Pre- and post-tests were administered to a sample of 11th graders of Vocational High Schools. The findings showed that the TED Talks videos had an effective effect on improving students' listening skills. A significant number of students demonstrated the potential to enhance their vocabulary and their comprehension of various accents. Moreover, engaging in listening can empower students